Structural Equation Modeling (SEM) Analysis Of Creative Video Competition Event On The Brand Image Of "Bogor Sport And Tourism" As Branding Bogor Regency - Mariana Rista Ananda Siregar; Imani Satriani (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The purpose of this research is to find out how the Bogor Regency branding campaign (city branding) "Bogor Sport and Tourism" can shape the brand image of Bogor Regency as a sports and tourism destination through the activity of "Creative Video and Singing Competition" about tourist destinations in Bogor Regency. This activity is one of the efforts to build its destination brand in terms of communication with its city branding stakeholders (city branding). The stimulus-response theory was used in this title-related research. This is a quantitative study that uses PLS-SEM data analysis. This study's population consisted of 67 participants who had gone through the selection stage to determine the winner. The study employed quota sampling. The findings revealed that the government must continue improving event marketing to improve brand image. According to the research findings, brand image improves when event marketing performance is successful. Event marketing can be strengthened by strengthening its forming constructs: individual, innovation, integrity, intensity, interaction, and involvement. At the same time, brand image can be seen in infrastructure, landscape, structure, and behavioural aspects.